ISDN2014_0300: REMOVED: White matter connectivity in dyslexia. Issue 47 (5th November 2015) - García‐Pentón, L.; Pérez, A.; Lerma, G.; Paz‐Alonso, P.M.; Iturria‐Medina, Y.; Carreiras, M.
Abstract : This article has been removed: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our‐business/policies/article‐withdrawal ) This meeting abstract has been removed by the Publisher. Due to an administrative error, abstracts that were not presented at the ISDN 2014 meeting were inadvertently published in the meeting's abstract supplement. The Publisher apologizes to the authors and readers for this error.